The Effect of Food Blogger’s Reviews on Young Adults’ Food Choice Decision in Malaysia - Ng Jia Miin, Janice; Ahmad, Rohizan; A/P Shamugam, Gogulamathe (International Journal of Psychosocial Rehabilitation, 2020)
A blog (a combination words of web and log) is a web page with regular diary or journal entries that incorporates different postings by authors and responses (Boas, 2011). The first blog was created by Justin Hall through Links.net where he shared about his family background and experience of his summer trip (Chapman, 2011). Blogging has become one of the most well-liked and prominent platforms for sharing contents on personal thought, feelings, opinions, and more. To date bloggers wrote reviews of products and services that they had used and experienced. Food blogger has been growing rapidly and popular among Malaysian. The reliant on technology especially by young adults in utilizing online media to search for information has led to a greater number of food bloggers in Malaysia. There are also concern among marketers as to the impact of food bloggers on blog’s readers. Thus, this research aims to examine the effect of perceived usefulness, trustworthiness and reputation of food blogger on young adults’ food choice decision making in Malaysia. The outcome of this study is also expected to contribute towards effective marketing strategies to marketers of food and beverage industry. In this research, Technology Acceptance Model (TAM) developed by Fred Davis was used to forecast an individual user acceptance of technologies. Overall findings concluded that all188 respondents showed that perceived usefulness, trustworthiness and reputation have strong correlation with teenager’s food choice decision.